STRATEGIC MANAGEMENT IN THE MODERN ECONOMIC DEVELOPMENT OF STATES - SYNIHOVETS, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to summarize the foundations of strategic management and its development in order to ensure effective activity under the influence of modern transformational processes. The article discusses the most influential trends in modern development associated with the processes of globalization. Development in the context of globalization, modern challenges determine the goals of improving approaches to managing economic development. The content of strategic management in economic development is revealed. The importance of strategic management in the formation and implementation of economic development priorities is determined. The necessity of using modern management tools to ensure the sustainability of economic growth, the formation of competitive advantages on this basis and the introduction of foreign experience is highlighted. Strategic management is able to ensure activities in accordance with the mission, is a success factor in a competitive environment. The process of developing and implementing development strategies is implemented at different levels; nationwide, regional, municipal and corporate strategies are being implemented. Estimating costs based on strategic analysis is important when choosing a development strategy. Integration processes are associated with the possibility of risks and threats. Forms of capital export are direct and portfolio investments. For a transitional economy, investments to increase the economic and production potential are significant. Among other forms of international capital movement, the role of portfolio investment is growing sharply. The international movement of capital generates economic growth and is currently an important direction in the study of the economy, the impact of capital migration should be taken into account and the investment position of the country should be assessed. In Ukraine, there is a tendency for a significant predominance of direct investment in the country over direct investment from Ukraine.The results of the study showed that strategic development planning should be considered as the basis for ensuring success. Strategic planning is the process of modeling the future with the determination of goals and the concept of long-term development. Strategic planning is the process of modeling the future with the definition of goals and the concept of long-term development. The strategic system is also being developed to ensure economic security.
Keywords: strategic management; economic development; economic development strategies; strategic planning; globalization and innovative development; international business; business efficiency